The Use of Active Learning Method in Teaching English Speaking Skill - Reni Safitri; Absharini Kardena; Gustina Gustina (Education : Jurnal Sosial Humaniora dan Pendidikan, 2023)
. The purpose of the study was to know the intended to find out the description about the process of teaching speaking skill using active learning method that is applied by the researcher. In this study the researcher conducted quantitative research and the method used was a quasi-experimental design, which focused on the results obtained by students. Where the sample consisted of 37 children. The instrument of data collection is through a test where each students get all the test from the researcher to speaking every time the researcher get to do this research. To get a score researcher give all the students change to it involves students directly and actively in the learning process itself. This means that instead of simply receiving information verbally and visually, students are receiving and participating and doing. The result of this study showed that there ware 81.14 % from these results indicating that the used of active learning method in teaching speaking skill.